Understanding The Diagnosis And Treatment of Conjunctival Capiler Hemangioma - Ananda Audia Arsiazi, Baiq (Jurnal KESANS : Kesehatan dan Sains, 2022)
Conjunctival hemangiomas are rare tumors that present at birth with reddish lesions that can grow in size over the next few months and spontaneously involute by 4-5 years of age. Symptoms of this tumor can be asymptomatic or can also cause visual disturbances if it has grown to be large. Capillary hemangiomas are more common in women and in premature or low birth weight infants. Both are associated with cardiorespiratory and hematological disorders. This tumor rarely attacks the age of over 60 years, but is more common in newborns. The diagnosis of hemangioma in addition to clinical symptoms, can also be established by supporting examinations. Treatment or management of these tumors depends on the presumptive diagnosis, size, growth, extent of the lesion, and the nature of the tumor.